PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN HEALTHCARE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Afrida, Fenny (STIE Mahardhika, 2024)
This research aims to examine the influence of financial performance, measured by Return On Assets (ROA), Net Profit Margin (NPM), and Debt to Equity Ratio (DER), on the stock prices of Healthcare companies listed on the Indonesia Stock Exchange during the period 2021-2022. The study employs purposive sampling as the method and adopts a quantitative approach, utilizing secondary data. The results of the research, analyzed through multiple linear regression, indicate that ROA, NPM, and DER do not have a significant impact on stock prices for Healthcare companies listed on the Indonesia Stock Exchange during the period 2021-2022.